Incidence of thyroid adverse events following immune checkpoint inhibitor treatment in patients with baseline positive thyroid antibodies: a systematic review and meta-analysis - Yu, Hui; Chen, Qichao; Hu, Wenbing; Chen, Yuanhao; Ming, Hui (Frontiers in Oncology, 2025)
BackgroundTo systematically evaluate the incidence of thyroid adverse events in patients with baseline positive thyroid antibodies following treatment with immune checkpoint inhibitors (ICIs).MethodsIn this systematic review and meta-analysis, we utilized PubMed, Embase, and Cochrane Library databases to identify studies that detail the thyroid immune-related adverse events (irAEs) among cancer patients undergoing treatment with ICIs. Literature was screened according to inclusion and exclusion criteria, and data were extracted. Meta-analysis was conducted using RevMan 5.4 and Stata 16.0 software, with adherence to PRISMA 2020 guidelines.ResultsA total of 13 studies involving 2,059 patients treated with ICIs for malignancies were included, with 594 cases of thyroid irAEs reported post-treatment. Meta-analysis revealed that the incidence of thyroid irAEs in patients with baseline positive thyroid antibodies was 66.7% (95% CI: 45.1%, 85.5%; Z=7.825, p<0.001). Subgroup analysis indicated that heterogeneity was influenced by geographic region, tumor type, and study type. In an exploratory analysis of 4 studies, thyroglobulin antibody (TgAb) positivity showed a numerically higher risk (but statistically non-significant) of thyroid irAEs compared to thyroid peroxidase antibody (TPOAb) positivity (OR=1.83, 95% CI: 0.87–3.85; Z=1.58, p=0.114), but the small number of studies precludes definitive conclusions.ConclusionPatients with baseline positive thyroid antibodies experience a higher incidence of thyroid irAEs following ICI treatment. In comparison to TPOAb, baseline TgAb positivity showed a non-significant trend toward higher thyroid irAE risk (based on limited studies), but further evidence is needed to confirm this relationship.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42025635209.